Efectos de la educación en el control prenatal y los resultados en la atención del parto de bajo riesgo (2021)
The objective of this work is to identify the effects of education on prenatal control and the results in low-risk delivery care. Design: This study is described as a narrative review of the literature within the Evidence-Based Nursing methodology.